Cell Growth Inhibition by Farnesyltransferase Inhibitors Is Mediated by Gain of Geranylgeranylated RhoB - Du, Wei (American Society for Microbiology, 1999)
Recent results have shown that the ability of farnesyltransferase inhibitors (FTIs) to inhibit malignant cell transformation and Ras prenylation can be separated. We proposed previously that farnesylated Rho proteins are important targets for alternation by FTIs, based on studies of RhoB (the FTI-Rho hypothesis). Cells treated with FTIs exhibit a loss of farnesylated RhoB but a gain of geranylgeranylated RhoB (RhoB-GG), which is associated with loss of growth-promoting activity. In this study, we tested whether the gain of RhoB-GG elicited by FTI treatment was sufficient to mediate FTI-induced cell growth inhibition. In support of this hypothesis, when expressed in Ras-transformed cells RhoB-GG induced phenotypic reversion, cell growth inhibition, and activation of the cell cycle kinase inhibitor p21WAF1. RhoB-GG did not affect the phenotype or growth of normal cells. These effects were similar to FTI treatment insofar as they were all induced in transformed cells but not in normal cells. RhoB-GG did not promote anoikis of Ras-transformed cells, implying that this response to FTIs involves loss-of-function effects. Our findings corroborate the FTI-Rho hypothesis and demonstrate that gain-of-function effects on Rho are part of the drug mechanism. Gain of RhoB-GG may explain how FTIs inhibit the growth of human tumor cells that lack Ras mutations.